2017
DOI: 10.18280/mmc_b.860309
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Fluid Flow and Heat Transfer inside a Saturated Porous Conduit at Constant Surface Heat Flux

Abstract: The fluid flow and heat transfer inside a saturated porous impermeable conduit at constant surface heat flux was modeled analytically and numerically. The present model was depicted the fluid flow and the temperature distribution through both of the entrance region and the fully developed region. The Nusselt number was found in both regions subjected to constant surface heat flux boundary condition. The present modeling was developed by using; the Continuity, Momentum and Energy equations. The equations were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Recently, a study by AlMasa’deh and Duwairi 7 demonstrated analytically and numerically flow of fluid and heat transfer within a saturated porous medium impenetrable conduit at a fixed heat flux. Besides, the mathematical study was performed to figure out the slip effects and radiation in a fully developed incompressible Newtonian fluid Williamson flow.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study by AlMasa’deh and Duwairi 7 demonstrated analytically and numerically flow of fluid and heat transfer within a saturated porous medium impenetrable conduit at a fixed heat flux. Besides, the mathematical study was performed to figure out the slip effects and radiation in a fully developed incompressible Newtonian fluid Williamson flow.…”
Section: Introductionmentioning
confidence: 99%
“…AlMasa'deh and Duwairi 13 modeled and solved analytically a two‐dimensional flow of Williamson fluid over a stretching sheet. The influence of different sizes of nanoparticles was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This value was 26.42% greater than EG-PW with base fluid alone. AlMasa'deh and Duwairi 16 analytically and numerically studied the fluid flow and heat transfer inside a porous conduit with heat flux. Through the completely formed and entry regions, the energy, momentum, and continuity equations were solved using a theoretical model with constant heat flux boundary conditions.…”
Section: Introductionmentioning
confidence: 99%